Regenerative fertilization strategies for climate-smart agriculture: Consequences for greenhouse gas emissions from global drylands. (20th April 2023) - Iqbal, Shahid; Xu, Jianchu; Khan, Sehroon; Worthy, Fiona Ruth; Khan, Haroon Zaman; Nadir, Sadia; Ranjitkar, Sailesh
Abstract: Cultivated drylands are significant sources of greenhouse gases (GHGs), with declining yields. Regenerative practices are vital to achieve joint goals of boosting yields and mitigating GHGs emissions. Nevertheless, studies usually consider crop yields and soil properties, often lacking quantitative analysis of GHGs. This meta-analysis used log response ratio (lnRR) to perform effect size statistics; assessing impacts of major regenerative (manure, biochar, and two integrated applications) and inorganic fertilizers on GHGs emissions. The results reveal that GHGs emissions were increased by fertilizer or manure addition, but biochar decreased GHGs emissions, with greatest benefit at 50 t ha −1 . Combining biochar or manure application with fertilizer emitted CO2 and/or N2 O. Applying biochar alone led to 144% reduction in global warming potential (GWP). Paddy-rice with fertilizer emitted N2 O and CH4, whereas these were mitigated by wheat with biochar. Fine-textured soils with manure emitted all three GHGs, whereas biochar with coarse-textured soils reduced emissions. Medium-textured soils had reduced N2 O (18%) and CH4 (25%) emissions with integrated biochar and fertilizer. CO2 and N2 O emissions were highest for neutral and acidic soils with fertilizer but lowest for alkaline soils after biochar application. Soil C:N ratios affected the best strategy to minimize GHGs: for high C:N ratio, fertilizer or manure should be avoided, in favour of biochar. Yet integrated biochar and fertilizer should be avoided for soils with low C:N ratio. We conclude that regenerative strategies using manure risk converting global drylands into major GHGs emitters. However, strategies incorporating biochar could mitigate dryland GHGs emissions and minimize GWP. Graphical abstract: Image 1 Highlights: Meta-analysis on regenerative agriculture showed biochar mitigated GHGs by 25-52%. Manure ± inorganic fertilizer increased CO2 and N2 O emissions by 74-89%. Wheat with biochar mitigated N2 O and CH4 30-45%, but manure emitted 16-61% GHGs. Fine-textured soils with manure addition had high N2 O and CH4 emissions 32-85%. Biochar with/without inorganic fertilizer reduced global warming potential 40-144%.